Induction of reversible bidirectional social approach bias by olfactory conditioning in male mice. (2nd January 2020) - Chan, Justin; Stout, Dawson; Pittenger, Steven T.; Picciotto, Marina R.; Lewis, Alan S.
ABSTRACT: Social avoidance is a common component of neuropsychiatric disorders that confers substantial functional impairment. An unbiased approach to identify brain regions and neuronal circuits that regulate social avoidance might enable development of novel therapeutics. However, most paradigms that alter social avoidance are irreversible and accompanied by multiple behavioral confounds. Here we report a straightforward behavioral paradigm in male mice enabling the reversible induction of social avoidance or approach with temporal control. C57BL/6J mice repeatedly participated in both negative and positive social experiences. Negative social experience was induced by brief social defeat by an aggressive male CD-1 mouse, while positive social experience was induced by exposure to a female mouse, each conducted daily for five days. Each social experience valence was conducted in a specific odorant context (i.e. negative experience in odorant A, positive experience in odorant B). Odorants were equally preferred pre-conditioning. However, after conditioning, mice sniffed positive experience-paired odorants more than negative experience-paired odorants. Furthermore, positive- or negative-conditioned odorant contexts increased or decreased, respectively, the approach behavior of conditioned mice toward conspecifics. Because individual mice undergo both positive and negative conditioning, this paradigm may be useful to examine neural representations of social approach or avoidance within the same subject.